Polecenie panowania nad stworzeniem (Rdz 1,26-28) w ekologicznej hermeneutyce Biblii - Twardziłowski, Tomasz (Collectanea Theologica, 2017)
The divine command given to a man (cf. Gen 1:26-28) has been a matter of concern in biblical scholarship for centuries. In the last decades, theologians and biblical scholars have tried to re-read this passage in view of the environmental crisis. This paper starts with an overview of the development of a new proposal – the ecological hermeneutics of the Bible. Particular paragraphs present results of the application of various ecological hermeneutical forms to the passage Gen 1:26-28: apologetic, radical and revisionist (neo-orthodox). The apologetic form perceives the text of the Bible as a friendly one to the environment and develops the idea of responsible human stewardship. It emphasizes the role of man as a custodian of creation. The radical form, by contrast, perceives the same texts as infected anthropocentrically. The order of command over creation introduces enmity between man and nature that is disclosed through exploitation and injustice towards the earth from the part of humankind. Therefore, it proposes a reconstruction of the text retrieving the voice of the earth. Representatives of a revisionist form claim instead that the passage Gen 1:26-28 re-read in the context of Gen 1-9 does not allow people to exploit the natural environment and it criticizes peoples’ behavior towards creation. The analysis shows that reading the divine command of human dominion in Gen 1:26-28 in a hermeneutical light considering the circumstances and specificity of the biblical text means neither the justification of the degradation of the natural environment, nor the refraining from gaining benefits from its natural resources.